Marine Algal Antioxidants as Potential Vectors for Controlling Viral Diseases - Clementina Sansone; Christophe Brunet; Douglas M. Noonan; Adriana Albini (MDPI AG, 2020)
As the COVID-19 epidemic expands in the world, and with the previous SARS epidemic, avian flu, Ebola and AIDS serving as a warning, biomedical and biotechnological research has the task to find solutions to counteract viral entry and pathogenesis. A novel approach can come from marine chemodiversity, recognized as a relevant source for developing a future natural "antiviral pharmacy". Activities of antioxidants against viruses can be exploited to cope with human viral infection, from single individual infections to protection of populations. There is a potentially rich and fruitful reservoir of such compounds thanks to the plethora of bioactive molecules and families present in marine microorganisms. The aim of this communication is to present the state-of-play of what is known on the antiviral activities recognized in (micro)algae, highlighting the different molecules from various algae and their mechanisms of actions, when known. Given the ability of various algal molecules-mainly sulfated polysaccharides-to inhibit viral infection at Stage I (adsorption and invasion of cells), we envisage a need to further investigate the antiviral ability of algae, and their mechanisms of action. Given the advantages of microalgal production compared to other organisms, the opportunity might become reality in a short period of time.